Production of Synbiotic Yogurt-Like Using Indigenous Lactic Acid Bacteria as Functional Food - M Astawan; T Wresdiyati; . Suliantri; I I Arief; R Septiawan (Faculty of Animal Science, Bogor Agricultural University, 2012)
Yoghurt is a product of fermented milk using Lactobacillus bulgaricus and Streptococcus thermophilus as culture starter. Indigenous probiotic lactic acid bacteria, Lactobacillus plantarum 2C12 or Lactobacillus acidophilus 2B4, were applied in the making of functional synbiotic yoghurt-like with 5% of fructo-oligosaccharide (FOS) as a prebiotic source. The aim of this study was to determine the best formula of functional synbiotic yoghurt-like among four formulas: F1 (L. bulgaricus + S. thermophilus), F2 (L. bulgaricus + S. thermophilus + L. plantarum 2C12), F3 (L. bulgaricus+ S. thermophilus + L. acidophilus 2B4), and F4 (L. bulgaricus + S. thermophilus + L. plantarum 2C12 + L. acidophilus 2B4) to be choosen and followed detection of it's flavor to improve the product quality and consumer acceptance. The results showed that the F3 synbiotic yogurt made from mixed culture L. bulgaricus, S. thermophilus, and L. acidophilus 2B4 had the highest antibacterial effect against Enteropathogenic Escherichia coli (EPEC). Addition of 1.75% natural corn starch as a stabilizer produced optimum improvement in yoghurt consistency and minimize whey separation. Result of sensory evaluation indicated that the yoghurt with addition of 1% strawberry flavor and 0.1% vanilla flavor were ranked at first and second. Yoghurts were still good to be consumed after 15 d storage period at the refrigeration temperature (10 oC).